2007
DOI: 10.1007/s11864-007-0033-1
|View full text |Cite
|
Sign up to set email alerts
|

Focal or Subtotal Therapy for Early Stage Prostate Cancer

Abstract: Focal treatment for prostate cancer is highly intriguing, but poorly supported by the published literature. Further studies, preferably randomized controlled trials, are needed before this can be considered standard therapy. Focal treatment should be reserved for patients with focal disease. Even "clinically insignificant" synchronous tumors are malignant, and carry risk of progression if not treated with the index lesion. Whether these are likely to progress in this setting compared to those managed with acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…For example, patients who underwent focal ablation had better erectile function before surgery. This was an expected finding as focal therapies aim to spare at least one NVB to preserve erectile function .…”
Section: Discussionmentioning
confidence: 68%
“…For example, patients who underwent focal ablation had better erectile function before surgery. This was an expected finding as focal therapies aim to spare at least one NVB to preserve erectile function .…”
Section: Discussionmentioning
confidence: 68%
“…Thus, patients harboring a bilateral prostate cancer should not be excluded from non-surgical focal treatment, even with the current controversy that smaller secondary foci may remain untreated. 35 Genetic basis of focality Multifocality can be explained by either uniclonal or multiclonal expansion of tumor cells. The former hypothesis suggests that a single transforming event occurs in one cell with the spread of this clone through the prostate resulting in topographically distinct but genetically related tumors.…”
Section: Assigning Multifocalitymentioning
confidence: 99%
“…Therefore, advocacy of subtotal treatment with the knowledge that smaller secondary foci remain untreated continues to be controversial at present despite there being two phase ii prospective ethics committee approved trials assessing this in MD Anderson and university College london and are currently recruiting patients (nCT00987675, nCT00877682). 35 Furthermore, although the goal of focal therapy for prostate cancer is to selectively ablate known disease, it should be remembered that a field effect might occur in prostate cancer, that is neoplastic or paraneoplastic cells exist in the apparently histologically normal field adjacent to the tumor. Genetic alteration and molecular changes have been found in normal appearing prostate tissue adjacent to tumor, consistent with the possibility of a field effect.…”
Section: Transrectal Ultrasound-guided Biopsymentioning
confidence: 99%
“…Focal therapy is intended to be a tailored treatment, thereby avoiding overtreatment while cautiously providing awareness of potential undertreatment. 35,[39][40][41][42][43] In the absence of image-guided therapy, at present, a practical approach is hemiablation of the prostate leaving untreated an intact lobe that will be able to facilitate an acceptable level of QoL, including potency and urinary continence. Retrospective analysis of a few large prostatectomy databases demonstrated that some proportion of the patients (up to 20%) with low-risk PCa could be selected for hemiablation.…”
Section: Current Protocols Of Focal Cryoablationmentioning
confidence: 99%